2023
DOI: 10.3389/fcvm.2023.1172178
|View full text |Cite
|
Sign up to set email alerts
|

Association between FIB-4, all-cause mortality, cardiovascular mortality, and cardiovascular disease risk among diabetic individuals: NHANES 1999–2008

Lihua Guan,
Lei Li,
Yutong Zou
et al.

Abstract: BackgroundDiabetes is prevalent worldwide and is associated with cardiovascular disease (CVD). Furthermore, due to the insulin resistance, diabetic populations are vulnerable to liver fibrosis, which increases the risk of CVD. Fibrosis-4 index (FIB-4)—a non-invasive biomarker for liver fibrosis—is crucial in predicting CVD among patients with liver diseases. However, the association between FIB-4, death, and CVD in the US diabetic population has not yet been investigated.MethodWe conducted a cross-sectional st… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(4 citation statements)
references
References 36 publications
0
4
0
Order By: Relevance
“…A recent study revealed that diabetic patients are more likely to develop liver fibrosis. 18 Our results showed that the most common underlying disease was diabetes mellitus, accounting for 50.7% and 50.0% of the blood culture-positive and sepsis groups, respectively. Insulin regulates glucose intake in the liver.…”
Section: Discussionmentioning
confidence: 55%
“…A recent study revealed that diabetic patients are more likely to develop liver fibrosis. 18 Our results showed that the most common underlying disease was diabetes mellitus, accounting for 50.7% and 50.0% of the blood culture-positive and sepsis groups, respectively. Insulin regulates glucose intake in the liver.…”
Section: Discussionmentioning
confidence: 55%
“…Around 55.48% of T2DM patients also have NAFLD. The prevalence of advanced liver fibrosis is notably higher in patients with both T2DM and NAFLD (17.02%) compared to those with only T2DM (4.80%) [22,23].…”
Section: Discussionmentioning
confidence: 94%
“…Furthermore, liver fibrosis can increase the risk of cardiovascular disease (CVD). Therefore, diabetic patients with liver fibrosis may face a significantly higher risk of developing CVD [22,24].…”
Section: Discussionmentioning
confidence: 99%
“…Liver fibrosis, caused by abnormal liver fat metabolism, may lead to abnormal accumulation of liver fat, resulting in inflammation, glucose metabolism disorder and also eventually cause CVD occurrence to increase. 14 So, can fibrosis indicators predict the occurrence of MACCEs in clinic?…”
Section: Introductionmentioning
confidence: 99%